Development of a high-throughput MassARRAY-based single assay for the characterization of Streptococcus suis species and serotypes - Surasak Jiemsup; Kamonwan Lunha; Wiyada Chumpol; Nattakan Meekhanon; Anusak Kerdsin; Suganya Yongkiettrakul (Scientific Reports)
Abstract Streptococcus suis is a significant porcine pathogen and zoonotic agent responsible for infectious diseases in humans worldwide. It is classified into 29 serotypes, each with varying geographical prevalence and pathogenicity. Hence, serotyping of S. suis is crucial for active surveillance, outbreak monitoring, and infection control. This study developed a novel MassARRAY-based single assay to simultaneously identify S. suis species and differentiate all 29 serotypes. The assay targeted glutamate dehydrogenase (gdh) and recombination/repair protein (recN) for species identification, and capsular polysaccharide (cps) genes for serotyping. Based on single nucleotide polymorphisms (SNPs) at position 483 of cpsK gene, the assay accurately distinguished between two pairs of serotypes: ½ and 2, as well as 1 and 14. The assay, validated with genomic DNA from 105 whole-genome sequencing (WGS)-confirmed isolates, demonstrated 100% specificity and sensitivity for both species identification and serotyping. In the evaluation with 143 field isolates, the results demonstrated perfect agreement between the MassARRAY-based assay and WGS for species identification, with 100% sensitivity and specificity, and for serotyping, with 99.15% sensitivity and 100% specificity (κ-value = 0.98). The agreement between WGS-based serotyping and multiplex PCR serotyping was substantial (κ = 0.65). Moreover, the results showed that the limit of detection for both species and serotypes ranged from 1 to 10 pg of gDNA per reaction.